A smartphone application supporting patients with psoriasis improves adherence to topical treatment: a randomized controlled trial. (5th July 2018) - Svendsen, M.T.; Andersen, F.; Andersen, K.H.; Pottegård, A.; Johannessen, H.; Möller, S.; August, B.; Feldman, S.R.; Andersen, K.E.
Summary: Background: Adherence to topical psoriasis treatments is low, which leads to unsatisfactory treatment results. Smartphone applications (apps) for patient support exist but their potential to improve adherence has not been systematically evaluated. Objectives: To evaluate whether a study‐specific app improves adherence and reduces psoriasis symptoms compared with standard treatment. Methods: We conducted a randomized controlled trial (RCT, clinicaltrials.gov registration: NCT02858713). Patients received once‐daily medication [calcipotriol/betamethasone dipropionate (Cal/BD) cutaneous foam] and were randomized to no app ( n = 66) or app intervention ( n = 68) groups. In total, 122 patients (91%) completed the 22‐week follow‐up. The primary outcome was adherence, which was defined as medication applied ≥ 80% of days during the treatment period and assessed by a chip integrated into the medication dispenser. Secondary outcomes were psoriasis severity measured by the Lattice System Physician's Global Assessment (LS‐PGA) and quality of life, measured using the Dermatology Life Quality Index (DLQI) at all visits. Results: Intention‐to‐treat analyses using regression was performed. More patients in the intervention group were adherent to Cal/BD cutaneous foam than those in the nonintervention group at week 4 (65% vs. 38%, P = 0·004). The intervention group showed a greater LS‐PGA reduction than the nonintervention group at week 4 (mean 1·86 vs. 1·46, P = 0·047). A similar effect was seen at weeks 8 and 26, although it did not reach statistical significance. Conclusions: This RCT demonstrates that the app improved short‐term adherence to Cal/BD cutaneous foam treatment and psoriasis severity. Abstract : What's already known about this topic? Psoriasis affects 2–4% of the Western adult population, has detrimental socioeconomic effects and negatively affects quality of life. Topical corticosteroid/calcipotriol combinations are recommended first‐line treatments for mild‐to‐moderate psoriasis, but poor adherence to topical treatments result in low efficacy. Several smartphone applications (apps) are available to patients with psoriasis, but the adherence‐improving potential of this technology has not been evaluated in a randomized controlled setting. What does this study add? This randomized controlled trial investigates the effects of a supporting app on adherence to a once‐daily topical calcipotriol/betamethasone dipropionate cutaneous foam preparation over a 28‐day period. The app provided daily reminders and informed patients whether they had applied their treatment. Information on adherence was obtained with a chip attached to the dispenser that synchronized to the app. The app significantly improved adherence rates and reduced psoriasis severity in the short term. Linked Comment: Howland and Dellavalle. Br J Dermatol 2018; 179 :1025–1026. Respond to this article Plain language summary available online